Effect of IBDV infection on the interfollicular epithelium of chicken bursa of Fabricius. (27th November 2018) - Bódi, Ildikó; Felföldi, Balázs; Minkó, Krisztina; Benyeda, Zsófia; Nagy, Nándor; Kiss, Anna L; Palya, Vilmos; Oláh, Imre
ABSTRACT: In the chicken bursa of Fabricius (BF ), the interfollicular epithelium (IFE ) consists of cylindrical- and cuboidal-shaped cells. Among the cylindrical-shaped epithelial cells, mucus-producing and caveolin-1 (Cav-1 )-expressing cells can be distinguished. Occasionally, the cuboidal-shaped cells also express Cav-1, which suggests that they are precursors of both mucus-producing and Cav-1-expressing cells. Very virulent infectious bursal disease virus (IBDV ) impedes the differentiation of Cav-1-expressing cells and shifts the differentiation of cuboidal cells towards mucus-producing cells. In control birds exclusively, the IFE surface shows a mucous membrane, but after IBDV infection, the surfaces of both IFE and FAE are also covered by a mucous membrane. After IBDV infection, the cells of FAE also produce mucus, providing evidence for cell transformation. In late postinfection (pi ; 28 d pi), the Cav-1 expression returned in the IFE cells, whereas the follicle (the primary lymphoid organ) underwent atrophy. The appearance of the renewed Cav-1-positive cells is similar to that of the normal basal cell, but they randomly locate in different levels of IFE, suggesting the loss of epithelial polarity. Between days 2 and 7 pi, the Cav-1 expression in the endothelial cells of the cortico-medullary capillary web is variable, which may explain the hemorrhage in several infected birds. The IBDV infection stops the Cav-1 expression and subsequently the cholesterol efflux into the bursal lumen. In the infected birds, the high cholesterol level may further worsen the clinical syndrome of IBDV.